The relationship between language development and physical aggression among children with intellectual disability - Maryam Razmjoee; Sima Shahim; Leili Salmani Khanekahdani (Vesnu Publications, 2014)
Abstract   Introduction: One of the most common behavioral problems in children with intellectual disability is physical aggression. Physical aggression is described as behaviors such as hitting, kicking, throwing object and threatening with the intent to harm others. Physical aggression is related to the different factors such as language skills, which has been examined among intellectually disabled children in the present study. Materials and Methods: In a descriptive cross-sectional survey, 102 intellectually disabled children of 6 and 8 years old (51 girls and 51 boys) who satisfied the inclusion criteria were recruited from educational centers for children with intellectual disability in Shiraz by stratified sampling method (age and gender). The Test of Language Development-Primary: 3rd Edition (TOLD-3) and Overt and Relational Aggression Questionnaire were used to assess children. Data was analyzed by Pearson's correlation coefficient and independent t-test. Significance level was set at less than 0.05. Results: There was a negative and significant correlation between physical aggression and expressive language (p=0.008) and receptive language (p=0.019). Intellectually disabled children with the low level of expressive and receptive language skills are likely to express physical aggression. Furthermore, more boys than girls expressed physical aggression (p=0.014). There was no a significant difference among boys and girls in expressive and receptive language skills. Conclusion: There was a negative and significant correlation between physical aggression and expressive language and receptive language. In addition, poor expressive language skills among intellectual disabled girls can be considered as a facilitative factor in expressing their physical aggressive behaviors. However, there was no any relation between language skills and physical aggression among boys with intellectual disability.  Keyword: Children with intellectual disability, receptive language, expressive language, physical aggression